Quality of relationship on information technology outsourcing for organizational success in hospitality industry - Sukru Cetinkaya, A.; Ergul, M.; Uysal, Muzaffer (Emerald, 2014)
Purpose – This paper aims to investigate the effects of vendor – client relationship on organizational success in the hospitality industry. The relationship between vendors and clients regarding information technology outsourcing does not always go in harmony. In the viewpoint of hospitality practitioners, information technology (IT) providers do not necessarily abide by the given promises stated on contracts, all the time. The service flows, which are mostly generated by the lack of quality relationship between vendors and clients directly affect hotels’ organizational performance.Design/methodology/approach – Data were collected by an online survey and analyzed using multivariable statistics (path analysis) to determine the effects of service quality and relationship quality on outsourcing success, and its effect on organizational performance. Data from 102 valid responses received from ten different countries, representing 230 hotels in total were analyzed.Findings – Service quality and relationship quality, which are two dimensions of outsourcing relationships, were found to be positively related to outsourcing success (r = 0.60 and 0.70, p < 0.01, respectively) and intangible organizational performance (r = 0.20, p < 0.05; 0.26 and 0.27, p < 0.01, respectively).Research limitations/implications – The research was designed to investigate the IT outsourcing service receiver’s (client) perspective. The IT service provider’s (vendor) perspective is disregarded. Disturbance results are very high (i.e. more than 0.95). This may well be the case that certain facets of the outsourcing success construct are not adequately represented by the chosen indicators. Research results may reveal an idea about the research subject, in general, but may not be generalized to the wholeindustry due to its sampling size. Finally, the survey was conducted online, and all online research restrictions were applicable to this research such as receiving very limited response rates.Practical implications – The results of this research provide important information for practitioners in the hospitality industry and IT service providers. Relationship quality between vendor and client was observed to be the most determinant factor in IT outsourcing success.Social implications – The proposed model may well serve as a framework for further examining mediating and possible moderating variables.Originality/value – There is limited research in the previous literature investigating the relationship between information technology vendor and client, in terms of service quality and relationship quality in hospitality industry. This paper may serve to fill in this gap.